Crystallographic studies of shikimate binding and induced conformational changes in Mycobacterium tuberculosis shikimate kinase. - Dhaliwal, B; Nichols, C; Ren, J; Lockyer, M; Charles, I; Hawkins, A; Stammers, D (2004)
The X-ray crystal structure of Mycobacterium tuberculosis shikimate kinase (SK) with bound shikimate and adenosine diphosphate (ADP) has been determined to a resolution of 2.15 A. The binding of shikimate in a shikimate kinase crystal structure has not previously been reported. The substrate binds in a pocket lined with hydrophobic residues and interacts with several highly conserved charged residues including Asp34, Arg58, Glu61 and Arg136 which project into the cavity. Comparisons of our ternary SK-ADP-shikimate complex with an earlier binary SK-ADP complex show that conformational changes occur on shikimate binding with the substrate-binding domain rotating by 10 degrees. Detailed knowledge of shikimate binding is an important step in the design of inhibitors of SK, which have potential as novel anti-tuberculosis agents.